Hematochezia before the First Feeding in a Newborn with Food Protein-Induced Enterocolitis Syndrome - Masanori Mizuno; Hiroshi Masaki; Ryoko Yoshinare; Yujun Ito; Hideyuki Morita; Hiroyuki Yoshio (Thieme Medical Publishers, Inc., 2011)
The prevalence and incidence of food protein-induced enterocolitis syndrome (FPIES) are clearly not known; its onset before first feeding at birth especially has been rarely reported. A female newborn was referred to our institution due to blood-stained diarrhea before her first feeding at birth. Examination of the stool with Wright-Giemsa staining on day 6 revealed numerous fecal eosinophils, including Charcot-Leyden crystals. Lymphocyte stimulation test (LST) against cow's milk protein also showed positive values on day 12. The hematochezia resolved immediately after starting intravenous nutrition. She was fed with breast milk and extensively hydrolyzed formula and discharged from hospital on day 49. FPIES was diagnosed based on these symptoms and data. Our case was thought to have acquired allergic enterocolitis after sensitization in her fetal period, which caused severe FPIES triggered by the first intake of cow's milk soon after birth. The patient with FPIES presents atypical clinical findings, which is likely to cause misdiagnosis and delay of appropriate treatment. Heightened awareness and increased attention may be necessary to diagnose FPIES, even soon after birth. Evaluating fecal eosinophils and LST, which may be difficult to perform in every clinical hospital, is thought to be useful for the detection of FPIES without oral food challenge.